Sinocrassula jiaozishanensis (Crassulaceae), a new species from Yunnan Province, China - Wang, Jia-Guan; Chen, Chao; Wang, Yi; He, Zhao-Rong (Phytotaxa, 2022)
Sinocrassula jiaozishanensis, a new species from China, is described and illustrated. Molecular analysis and morphological comparisons were carried out. The new species can be easily distinguished from other Sinocrassula species by its basal leaves opposite, not rosulate, turquoise with apex red, flowering stems terminal, and nectar scales oblong to kidney-shaped.